Use of pectin for the spray delivery of mesenchymal stromal cells for brain injury - Nash, Amy Louise (2023)
Traumatic brain injury (TBI) occurs as a result of significant impact to the head causing damage to the brain tissue, such as that resulting from traffic collisions and falls, and can lead to long-term disability for affected patients. Current therapies for brain injury aim to limit further damage occurring via secondary injury pathways as a response to the initial trauma. Animal studies have shown improved neurological outcomes after injury following mesenchymal stromal cell (MSC) transplantation (Volkman, 2017) due to the immunomodulatory and pro-regenerative effects of the proteins and extracellular vesicles of the secretome (Pischiutta et al., 2022). Successful delivery of these cells is limited by the delivery route. Cells delivered intravenously show poor migration to the site of injury, resulting in a large loss of therapeutic cells (Harting et al., 2009). Therefore, it was hypothesised that spraying MSCs in a pectin solution would result in retained viability and phenotype of the cells, possibly offering a suitable method for local delivery of MSCs to TBI patients in the future. Pectin is cross-linkable with calcium, enabling cells to be sprayed in solution. In this thesis, four grades of citrus pectin were selected for evaluation, each with differing degrees of methylation (DM) and amidation (DA). CU-701 and CU-L have 37% and 28% DM respectively and LM-102 and LM-104 have 19% and 20% DM, and 30% and 27% DA respectively. The mechanical and biocompatibility properties of each of these grades was assessed, including viscosity, gelation, and cytotoxicity testing. Each grade demonstrated a viscosity suitable for spraying at 1% w/v in 1xPBS pH 7.4 and gelation with calcium was still observed. Since all grades of pectin (at 1% w/v in 1xPBS pH 7.4) showed low cytotoxicity, all grades were progressed to cell spraying studies. The mucosal atomisation device (MAD) syringe sprayer was selected for evaluation in the cell spraying experiments. The cell viability after spraying was assessed at a range of cell densities using the 3T3 mouse fibroblasts and the SH-SY5Y human neuroblastoma cell lines. Once viability was established, similar cell viability testing was carried out using primary human MSCs derived from the bone marrow of three separate donors, showing that high viability after spraying could be achieved at all cell densities tested. Studies then progressed to evaluate the viability and surface marker expression (CD90, CD105, CD73, CD34, CD11b, CD19, CD45, and HLA-DR) by flow cytometry of the hMSCs after spraying in pectin solutions. High viability, comparable to the hMSC seeded by syringe in 1xPBS, was achieved for all pectin grades. The results of the surface marker expression analysis showed CU-701 was the only grade of pectin not to show a significant downregulation of CD90, CD105, and CD73 compared to the control, or significant upregulation of CD34, CD11b, CD19, CD45, and HLA-DR. As a result, CU-701 pectin was taken forward into preliminary differentiation studies and a differential gene analysis. No spontaneous differentiation of the hMSCs into cells of an osteogenic or adipogenic lineage was observed as a result of seeding in CU-701 pectin or spraying. Preliminary data indicated the osteogenic differentiation may be impaired for one of the three donors, however adipogenic differentiation was observed in all conditions tested. Further studies are required to test for chondrogenic differentiation, to further test the osteogenic differentiation potential, and to include the hMSCs from the third donor. Differential gene expression analysis of approximately 30,000 genes was then carried out using cells which had been syringed or spraying in either 1xPBS or CU-701 pectin. This indicated that the process of spraying had very little effect on gene expression, but that the CU-701 pectin and the different donors caused genes to be differentially expressed. Using the SH-SY5Y cell line, in vitro models of oxidative stress and excitotoxicity were optimised and established. Pectin hydrogels were added to the damaged cells in culture, and the LM-102 and CU-701 pectin grades were selected for use in the co-culture model. Human MSCs were added to well inserts by syringe or spray in 1xPBS, LM-102, or CU-701 pectin to understand whether they influenced SH-SY5Y survival or proliferation after damage by glutamate or H2O2. No significant differences were observed, suggesting hMSCs may modulate repair following damage via alternative pathways. Overall, this study has demonstrated that viable hMSCs can be sprayed in different grades of pectin using the MAD syringe sprayer. The CU-701 grade appears to be most suitable for use with hMSCs based on experiments carried out in this thesis. This provides key information for the future development of spraying hMSCs in pectin as a local delivery method for use in TBI.